2016
DOI: 10.1093/acprof:oso/9780198732693.001.0001
|View full text |Cite
|
Sign up to set email alerts
|

Floral Mimicry

Abstract: Mimicry is a classic example of adaptation through natural selection. The traditional focus of mimicry research has been on defense in animals (protective mimicry), but there is now also a highly developed and rapidly growing body of research on floral mimicry in plants. Being literally rooted to one spot, plants generally have to use food bribes to cajole animals into acting as couriers for their pollen. Plants that lack these food rewards often deploy elaborate color and scent signals in order to mimic food … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
214
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(220 citation statements)
references
References 15 publications
5
214
1
Order By: Relevance
“…). However, the effects, and even existence, of such negative frequency dependence on the fitness of mimetic plants remain unclear (Johnson ; Peter & Johnson ; Johnson & Schiestl ).…”
Section: Introductionmentioning
confidence: 99%
“…). However, the effects, and even existence, of such negative frequency dependence on the fitness of mimetic plants remain unclear (Johnson ; Peter & Johnson ; Johnson & Schiestl ).…”
Section: Introductionmentioning
confidence: 99%
“…Within‐flower temperature is thus often 2–5°C higher than the ambient temperature. As a result, visits may be brief to avoid extended exposure to high temperatures (causing heat stress) within sunlit flowers, and insect temperature may decrease due to thermoregulatory cooling flights when solitary bees leave a flower (Corbet and Huang ).…”
Section: Discussionmentioning
confidence: 99%
“…All statistical analyses were performed in R ver. 3.5.1 (<http://www.r-project.org>) and we used the following functions: glmmadmb from the glmmADMB package to fit models following negative binomial distribution (Skaug et al ), lmer and glmer from lme4 to fit other (G)LMMs (Bates et al 2015), r.squaredGLMM from MuMIn to calculate coefficients of determination (Barton 2018) and testInteractions from phia for post hoc comparisons (De Rosario‐Martinez 2015). The statistical significance threshold was set at 0.05.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study has found that in Ophrys species sharing a common pollinator, morphological differences can maintain reproductive isolation (Gögler et al ., ). It appears, however, unlikely that if the floral scent barrier between Ophrys species, which rely on the sexual pheromone analogue for reproductive isolation, would break down, morphological differences alone would be able to filter out unspecific visitors (Cortis et al ., ; Johnson & Schiestl, ). Instead, our results suggest that flower form acts to maximize reproductive success in a system which is severely pollinator limited (Tremblay et al ., ).…”
Section: Discussionmentioning
confidence: 99%